Routine viral load monitoring versus standard care for reducing morbidity and mortality in adolescent and adult patients living with HIV on antiretroviral therapy (ART) - Adekanmbi, Victor (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine if routine viral load monitoring strategy is better than standard of care monitoring strategy at reducing morbidity and mortality in adolescent and adult patients living with HIV on 1st line ART.